Observational Trends in Publicly Reported Quality Measures of Hospital Outpatient Quality Reporting Program, 2013-2019. Issue 3 (July 2022) - Hamadi, Hanadi; Zhao, Mei; Haley, D. Rob; Xu, Jing; Paryani, Shyam; Spaulding, Aaron
Abstract : In 2011, the Centers for Medicare & Medicaid Services (CMS) implemented the Hospital Outpatient Quality Reporting Program to assess the quality of outpatient imaging efficiency (OIE). In this study, trends in hospital performance on these national hospital OIE measures a year after inception and public reporting were described. An observational trend analysis was conducted using 2013-2019 data from CMS 6 OIE measures. The trend analysis of metric scores indicates year-to-year variability in all 6 OIE variables. The reporting of these measures appears to have effectively improved the efficiency of most of the measures since the inception of the program.